2021
DOI: 10.1371/journal.ppat.1009941
|View full text |Cite
|
Sign up to set email alerts
|

TCA cycle remodeling drives proinflammatory signaling in humans with pulmonary tuberculosis

Abstract: The metabolic signaling pathways that drive pathologic tissue inflammation and damage in humans with pulmonary tuberculosis (TB) are not well understood. Using combined methods in plasma high-resolution metabolomics, lipidomics and cytokine profiling from a multicohort study of humans with pulmonary TB disease, we discovered that IL-1β-mediated inflammatory signaling was closely associated with TCA cycle remodeling, characterized by accumulation of the proinflammatory metabolite succinate and decreased concent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 57 publications
0
20
0
Order By: Relevance
“…Although IL-1β is host-protective during early stages of TB, as the disease progresses, it can enhance pro-inflammatory eicosanoid production, resulting in an influx of neutrophils and exacerbating tissue pathology 58 , 59 . In the case of human pulmonary TB, a recent study of patients with untreated multidrug-resistant M. tuberculosis found that IL-1β and pro-inflammatory eicosanoids correlated with tricarboxylic acid cycle remodelling 60 . Mitochondria are central to host immunometabolism as they house multiple metabolic pathways, impact cell death and inflammasome activation, and produce ROS 61 .…”
Section: How M Tuberculosis Establishes Infectionmentioning
confidence: 99%
“…Although IL-1β is host-protective during early stages of TB, as the disease progresses, it can enhance pro-inflammatory eicosanoid production, resulting in an influx of neutrophils and exacerbating tissue pathology 58 , 59 . In the case of human pulmonary TB, a recent study of patients with untreated multidrug-resistant M. tuberculosis found that IL-1β and pro-inflammatory eicosanoids correlated with tricarboxylic acid cycle remodelling 60 . Mitochondria are central to host immunometabolism as they house multiple metabolic pathways, impact cell death and inflammasome activation, and produce ROS 61 .…”
Section: How M Tuberculosis Establishes Infectionmentioning
confidence: 99%
“…Unusual activity of TCA cycle intermediates leads to the activation of in ammatory cells, which in turn leads to the up-regulation of proin ammatory factors [17,62]. There is evidence that the remodeling of TCA cycle is related to the secretion of pro-in ammatory IL-1β and the signal transduction of IFN-γ, while IL-1β and IFN-γ are pro-in ammatory cytokines that mediate different kinds of immune responses [73].…”
Section: Discussionmentioning
confidence: 99%
“…6D). TCA circulation pathway give scope to remarkable affect in mediating in ammatory response, and its effect on body function by regulating in ammation has been con rmed by many studies [33][34][35][36][37].…”
Section: Analysis Of Liver Tissue Proteomicmentioning
confidence: 99%
“…This effect is not seen with drug susceptible TB. While inflammatory signalling and TCA cycle remodelling occurs during drug susceptible TB infection, 2 months of ineffective treatment of MDR-TB resulted in a marked upregulation of this inflammatory cascade, an effect that took a year to reverse (Collins et al, 2021). These, and related effects, should be carefully investigated to develop appropriate health systems strategies for monitoring outcomes of drug resistant TB.…”
Section: Immunometabolismmentioning
confidence: 99%